1975
DOI: 10.2307/3279233
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Excretion of Neutral Lipids in the Metacercaria of Leucochloridiomorpha constantiae (Trematoda) Maintained In vitro

Abstract: Histochemical and thin-layer chromatographic analyses were made on neutral lipids in Leucochloridiomorpha constantiae (Trematoda) metacercariae incubated in non-nutrient Locke's solution at 37.5 or 42 C for 24 hr. As determined by Oil Red O staining, lipid droplets accumulate mainly in the intestine of incubated worms. Attempts to distinguish specific neutral lipid fraction of metacercariae obtained directly from snails is free sterol. During incubation, metacercariae accumulate triglycerides and to a lesser e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Our E-S analysis of H. medioplexus is in agreement with previous studies (Fried &Gioscia, 1976;Fried & Shapiro, 1975;Fried etal. 1980;Fried & Robinson, 1981), which indicated that sterol is a major lipid fraction released by flukes into a non-nutrient medium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our E-S analysis of H. medioplexus is in agreement with previous studies (Fried &Gioscia, 1976;Fried & Shapiro, 1975;Fried etal. 1980;Fried & Robinson, 1981), which indicated that sterol is a major lipid fraction released by flukes into a non-nutrient medium.…”
Section: Discussionsupporting
confidence: 93%
“…Either 5, 10 or 20 /A aliquots of the lipophilic fraction of the worm-free incubation material, or Locke's 1:1 control, or worm extract were applied to t.l.c. sheets using calibrated disposable micropipettes (Fried & Shapiro, 1975) along with the neutral lipid standard 18-4A (Nu-Chek-Prep., Inc., Elysian, Minnesota, USA), containing equal amounts of cholesterol, oleic acid, triolein, methyl oleate and cholesteryl oleate. Chromatograms were developed 10 cm from the origin and lipids were detected by spraying chromatograms with 5 % (v/v) phosphomolybdic acid in ethanol (Kritchevsky & Kirk, 1952).…”
Section: Methodsmentioning
confidence: 99%
“…analysis. A total of 300 metacercariae was incubated (10/tube) in 0-2 ml of sterile Locke's solution for 1 h at 37 + 1 °C (Fried & Shapiro, 1975) and the worm-free incubate material was combined and extracted in 60 ml of chloroform-methanol (2:1). The hydrophilic and lipophilic layers were separated and the hydrophilic layer was reduced by 50 % under nitrogen and was stored at -20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The free (unencysted) metacercariae of Leucochloridiomorpha constantiae (Brachylaimidae) pair in vitro (Fried & Roberts, 1972), accumulate neutral lipid in the intestinal caeca and. egest it into the culture medium (Fried & Shapiro, 1975), and is attracted to free sterol worm products (Fried & Gioscia, 1976). We have recently obtained a related brachylaimid, Amblosoma suwaense, from Campeloma decisum snails in Wisconsin by courtesy of Dr William F. Font.…”
Section: Introductionmentioning
confidence: 99%
“…Certain trematode species are able to excrete lipids via the excretory canal (Fried and Shapiro 1975, Fried and Appel 1977, whereas mature cestodes accumulate lipids in the parenchymal cells. The parenchymal concentration of lipids increases progressively with the maturity of the proglottids.…”
Section: Discussionmentioning
confidence: 99%